Acute change in glomerular filtration rate with inhibition of the renin-angiotensin system does not predict subsequent renal and cardiovascular outcomes - Clase, Catherine M.; Barzilay, Joshua; Gao, Peggy; Smyth, Andrew; Schmieder, Roland; Tobe, Sheldon; Teo, Koon K.; Yusuf, Salim; Mann, Johannes (Kidney International, 2017)
Initiation of blockade of the renin-angiotensin system may cause an acute decrease in glomerular filtration rate (GFR): the prognostic significance of this is unknown. We did a post hoc analysis of patients with, or at risk for, vascular disease, in two randomized controlled trials: Ongoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial (ONTARGET) and the Telmisartan Randomized AssessmeNt Study in ACE iNtolerant participants with cardiovascular Disease (TRANSCEND), whose median follow-up was 56 months. In 9340 patients new to renin-angiotensin system blockade, who were then randomized to renin-angiotensin system blockade, a fall in GFR of 15% or more at 2 weeks after starting renin-angiotensin system blockade was seen in 1480 participants (16%), with persistence at 8 weeks in 700 (7%). Both acute increases and decreases in GFR after initiation of renin-angiotensin system blockade were associated with tendencies, mostly not statistically significant, to increased risk of cardiovascular outcomes, which occurred in 1280 participants, and of microalbuminuria, which occurred in 864. Analyses of creatinine-based outcomes were suggestive of regression to the mean. In more than 3000 patients randomized in TRANSCEND to telmisartan or placebo, there was no interaction between acute change in GFR and renal or cardiovascular benefit from telmisartan. Thus, both increases and decreases in GFR on initiation of renin-angiotensin system blockade are common, and may be weakly associated with increased risk of cardiovascular and renal outcomes. Changes do not predict increased benefit from therapy.
EVALuna2:3927